Some Classes of Schwarzian Functions and its Coefficient Inequality that is Sharp - Gurmeet Singh, Misha Rani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In our present work, we defined an inequality called Fekete – Szegö Inequality for the functions f (z) associated with the class of starlike functions, along with their extremal functions and some subclasses.